The Relationship Between Contraceptive Features Preferred by Young Women and Interest in IUDs: An Exploratory Analysis. Issue 3 (7th July 2014) - Gomez, Anu Manchikanti; Clark, Jennifer B.
<x xml:space="preserve">Abstract</x> CONTEXT Little research has examined the relationship between women's preferences of contraceptive features and their interest in IUD use. Given high levels of contraceptive discontinuation and dissatisfaction, a better understanding of contraceptive preferences may support women in finding their optimal method and meeting their family planning goals. METHODS Data from 382 heterosexual women aged 18–29 were collected via a 2012 Internet survey. Chi‐square tests and multivariate, multinomial logistic regression models were used to examine relationships between contraceptive features preferred by women and their interest in IUD use. RESULTS Forty‐eight percent of women reported being unsure whether they would ever use an IUD; 20% were interested in using one, and 32% were not. In multivariate analyses, characteristics of a contraceptive method found positively associated with IUD interest were the method's not interfering with sexual pleasure (relative risk ratio, 3.4), being 99% effective without user action (2.5) and being effective for up to five years without any user action (3.8). Women who preferred a method that they could see or that would allow them to resume fertility immediately after discontinuation were less likely than those who did not to be interested in using rather than not using an IUD (0.4–0.5). CONCLUSIONS The findings of this exploratory analysis indicate that women value a multitude of contraceptive features, which may have implications for their interest in using an IUD. Future research should consider the ways that women's contraceptive preferences can be incorporated into contraceptive counseling.